Continuity and Change in the Development of the Turkish Secularism (Czech Journal of International Relations, 2010)
The study explores the specifics of the Turkish secularism as compared tothe general definition of the concept of secularism. By analysing thepolitical and social development of modern Turkey, the authordemonstrates the transformation of the Turkish secularism in the face ofpolitical and social pressures. From the study's point of view the Turkishsecularism does not represent a static phenomen by any means, but it israther a changing concept and policy which was profoundly influenced bythe notions of Kemalist modernisation and Turkish nationalism above allelse. The study presumes that the Turkish secularism remains subject tochange and adaptation as these concepts evolve and possibly lose theirsignificance at the cost of other political concepts gaining in significance.
Keywords: Turkey; securalism; Islam; Kemalism; AKP; modern history